Avaliação histopatológica da cápsula posterior associada ao implante de lente intraocular com superfície modificada com plasma de flúor e polietilenoglicol em coelhos - Souza, V. L. [UNESP]; Pellizzon, C. H. [UNESP]; Sereno, M. G. [UNESP]; Soares, R. T. [UNESP]; Ranzani, J. J.T. [UNESP]; Rodrigues, A. C.L. [UNESP]; Padovani, C. R. [UNESP]; Brandão, C. V.S. [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the effect of surface treatment of acrylic intraocular lens using Fluorine plasma or polyethylene glycol in the prevention of posterior capsule opacification. Forty rabbit eyes that underwent phacoemulsification were analyzed and distributed into four experimental groups (n=10): Control group, composed of rabbits without intraocular lens implantation; intraocular lens group treated with Polyethylene glycol plasma, intraocular lens group treated with Fluoride plasma, and commercial intraocular lens group. The posterior capsule of the lens was evaluated by histopathological analysis, including morphometric and immunohistochemical studies. Groups with intraocular lens treated with polyethylene glycol and commercial intraocular lens presented thinner posterior capsule at initial assessment (12 weeks) compared to the control group. At the end of the evaluation (six months), the treatment of surface intraocular lens with fluorine and polyethylene glycol plasma did not reduce the development of histological changes associated with posterior capsule opacification. The surface treatment of the intraocular lens with Fluoride and Polyethylene glycol can be performed as an adjuvant in preventing posterior capsule opacification, because it does not cause changes in the morphology of lens after phacoemulsification surgery.
Histopathological evaluation of posterior capsule associated with intraocular lens implant with modified surface using fluorine and poliethilene glycol plasma in rabbits
Keywords: Capsular; Immunohistochemistry; Morphometry; Opacification; Rabbit